Prevalence of obesity among undergraduate medical students in tertiary care hospital, Nandyal - Kundavaram, Chandra Bhanu; M. A., Mushtaq Pasha; Fatima , Afsar (International Journal Of Community Medicine And Public Health, 2023)
Background: Obesity is widely regarded as a major as a major global pandemic. It is associated with numerous comorbidities such as increased cardiovascular diseases and diabetes. Over 650 million adults of 18 years and older were obese. Methods: A cross sectional study was done among 1st, 2nd, 3rd year undergraduate medical students of a tertiary care hospital, Nandyal during August 2022 to September 2022. Sample size was 300. Weight and height of the participants were measured and data was collected using predesigned semi structured questionnaire and data was analysed using SPSS version 2022. Results: Out of 300 study participants,133 were males and 167 were females. 21 (7%) students had BMI<18.5 of which 16 students of age group 20-23 years were under weight, 5 students of age group 18-19 years were thin (BMI for age ≤2SD), 195 (65%) students were normal, 60 (20%) students were overweight and 24 (8%) students were obese. Conclusions: The prevalence of overweight and obesity were high in medical students. Prevalence of overweight and obesity were higher in females compared to males.